A Comprehensive Review of Rice Husk Derived Silica As Nano Filler (A review of literature) - Walaaldeen Khairi, Azza; jaafar naser, Huda; Abdul-Hamid Naji, Ghassan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Nowadays, the entire globe is suffering from two types of problems: excess waste production and a scarcity of virgin resources. Utilizing wastes in the primary industrial sector is one way for addressing these concerns from the viewpoints of developing nations’ ecosystems, energy demands, and economy. Natural fillers such as bamboo, rice husk, pistachio shells, and coir fiber have been reported to be efficient natural fillers. When natural materials are used as reinforcing materials, they offer advantages such as cost-effectiveness, high density, renewability, and a high degree of flexibility in the task, as well as a healthier working environment.